Computing some Laplacian Coefficients of Forests - Ali Ghalavand; Ali Reza Ashrafi (Journal of Applied Mathematics)
Let G be a finite simple graph with Laplacian polynomial ψG,λ=∑k=0n−1n−kckλk. In an earlier paper, the coefficients cn−4 and cn−5 for forests with respect to some degree-based graph invariants were computed. The aim of this paper is to continue this work by giving an exact formula for the coefficient cn−6.